The impacts of public expenditure innovations on real exchange rate volatility in South Africa - Nuru, Naser Yenus,Gereziher, Hayelom Yrgaw (United Nations University World Institute for Development Economics Research, 2021)
This study investigates the impacts of public expenditure innovations on exchange rate volatility in South Africa using quarterly data for the period 1970-2019. To achieve this objective, a version of the vector autoregressive impulse response model proposed by Jordà is employed and the innovations are identified recursively. The impulse response functions indicate that public expenditure innovation has a significant depreciating trend impact on exchange rate volatility, and its impact relies on the type of fiscal expenditure innovation. While the impact of public expenditure innovation on exchange rate volatility does not rely on the direction of the innovation, it varies according to the state of the economy. Public expenditure innovation has a depreciating trend impact on exchange rate volatility in the upturn state, and mostly an appreciating trend impact in the downturn state. The impact is greater in the upturn than the downturn state.
10.35188/UNU-WIDER/2021/010-8
Keywords: Graue Literatur; public expenditure; impulse response; exchange rate volatility; South Africa